Devolovment Language Indonesian Writing Materials at SD Negeri 060837 Medan - Harahap, Poppy Hasnah; Lenny Gusti Arini; Dewi Ramayani; Asni Nasution; Murni Hati Harahap; Juni Arpah; Ruth Mevy Sitorus; Julia Rahmadani (PT Inovasi Pratama Internasional, 2025)
During the learning process that makes students a little less interested in learning, and has not been developed the use of media and learning media can be described as media that contain information or instructional messages and can be used in the learning process. Learning media is a medium that conveys messages or information that contain the intent or purpose of learning. Learning media is very important in helping students acquire new concepts, skills, and competencies; therefore, researchers can understand that media is very important in learning. Many types of media can be used by teachers in the teaching and learning process, but teachers must be selective in choosing the type of media. In the digital era, teachers must be able to use not only classical learning media but also modern learning media. Several research findings also show the positive impact of media used as an integral part of classroom learning or as the main way learning takes place, and that learning media is one of the tools used by teachers so that learning activities take place effectively. Media is anything that can be used to channel messages from the sender to the recipient so that it can stimulate the thoughts, feelings, attention, and interest of students in such a way that the learning process occurs